Problematic of the development of the philosophy of diversity in modern and contemporary political thought : A study in the direction of support and opposition to it - Imad Ahmad Mawlood; Abid khalid Rasul (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Contemporary political thought includes two different views towards diversity; A positive, pluralistic view stems from the liberal-democratic political thought that views diversity as a source for defending the rights and freedoms of individuals and groups, and another negative view stems from the totalitarian political thought that views diversity as the basis for discrimination and the disintegration of the state. From this standpoint, the most prominent trends of the philosophy of diversity appear, which are limited to two different directions; A trend that recognizes diversity as a reality, but strongly opposes it in the context of defending a group to justify superiority under the pretext of (race, ethnicity, class, majority). And another trend supports diversity in its two parts (individual and collective), as is evident in the defense of individual and group liberalism for diversity and pluralism.